The Efficacy of Work from Home Policy in Managing Immigration Service Delivery - Gunawan Ari Nursanto; Arief Febrianto; Virra Wirdhiningsih; Muhammad Arief Hamdi; Seno Setyo Pujonggo (Journal Of Global Strategic Studies, 2026)
This study examines the effectiveness of Work from Home (WFH) policy in Indonesian immigration public service delivery, using Efficiency Theory and Digital Transformation Theory as frameworks for analysis. The findings suggest that WFH enhances administrative efficiency and supports digital transformation for remote-compatible functions such as visa processing, residence permit administration, and internal coordination. However, the policy proves less effective for front-line services requiring physical presence, such as passport issuance, biometric capture, and border control. The study highlights that WFH must be considered selectively based on the operational nature of each immigration function. Additionally, the effectiveness of remote work in immigration services is closely linked to digital readiness, cybersecurity, and the availability of secure infrastructure. The article concludes by proposing a function-based model for WFH implementation, emphasizing the need for continued investment in digital infrastructure and equitable access to immigration services. This study contributes to the understanding of WFH applicability in the public sector, specifically in immigration services, and offers policy recommendations for improving service delivery through hybrid work models.